(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
This article analyzes the key traits of Pere Gimferrer’s poetry through a commented poem from his book La muerte en Beverly Hills. This collection of poems is a clear example of the huge poetic renewal initiated by “Los Novísimos” in Spain, during the late 60’s. Through the inclusion of the new mass media into poetry and its merging with high culture, they managed to leave behind the narrow edges of social poetry and further explore the limits of language.